Longitudinal study of the influence of the relative age effect (RAE) on Czech tennis players aged 10-12. - Kolonicný, R. (Studia Sportiva, 2018)
The issue of the phenomenon known as RAE first appeared in research within the educational system. In the field of sports research, it first emerged in the 1980s. The theory of RAE is based on the assumption that athletes born in the early months of the year are usually more advanced in both mental and physical fitness. Many studies have confirmed that birthdates of players in sports such as handball, ice hockey or football are distributed asymmetrically in the respective quarters of the year. A high incidence of birthdates has been shown to exist in the first half of the year. The aim of the study was to determine the impact of RAE on Czech tennis players in the age category of 10 - 12. The investigated sample consisted of players (n=1 500) who ranked among the top one hundred in the official ranking of the Czech Tennis Association in the period of 2003 - 2017. In order to verify the conformity of the distribution of the frequency of the players´ birthdates in the sample and the frequency of birthdates among the same population (n=1 506 504) the Chi-Square test (?2) was used. The results of the study have shown a significant influence of RAE in certain years in the reference age category of 10 - 12, and in thirteen of the fifteen years surveyed. The overall results in the reference period 2003 - 2017 have shown that most of the players were born in Q1 (n=551) and Q2 (n=442). Therefore, 2/3 of the players (66%) were born in the first half of the year, while only 1/3 (34%) were born in the second half. A longitudinal study of tennis players aged 10 - 12 showed the influence of RAE both in specific years (with the exception of 2011 and 2014) and in the reference period 2003 - 2017 taken as a whole. The results of our research correspond to the results of similar studies performed by other authors. Tennis coaches are advised to address the issue of RAE when working with tennis youth and when selecting players to the sports centres, representations, etc.